PERFORMANCES AND ORGANOLEPTIC QUALITY OF VANARAJA CHICKEN UNDER DIFFERENT REARING SYSTEM (Indian Journal of Animal Production and Management, 2015)
A total of 120 day old chicks were utilized to evaluate the production performance of Vanaraja chickens under different rearing systems viz. cage, deep litter and semi intensive during 2009. The overall mean body weight, feed conversion ratio were recorded as 1323+28.02, 1238.12+46.02 and 1283.00+26.30 g; and 2.27, 2.44 and 2.05 for cage, deep litter and semi intensive systems respectively. Overall feed conversion ratio (FCR), protein efficiency ratio (PER) and energy efficiency ratio (EER) was significantly better (P
Keywords: Vanaraja; Rearing systems; Carcass characteristics; Economics